(untitled) (Cambridge, U.K.,New York, 2001)
Leading researchers examine child poverty in industrialized countries--the United States, UK, Germany, Ireland, Spain, Hungary, and Russia--in this major new study. Issues addressed are: definition and measurement in the dynamic analysis of child poverty; cross-national comparisons of child poverty rates and trends; cross-national comparisons of children's movements into and out of poverty; country-specific studies of child poverty dynamics; and the policy implications of taking a dynamic perspective. This unique study, with its cross-national and dynamic analysis of child poverty, will interest academics, international organizations, governments and their advisors
Keywords: Poor children,Children,Trẻ em nghèo,Trẻ em; Social conditions,Điều kiện xã hội